2014
DOI: 10.3109/14767058.2014.915936
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of pregnancy with history-indicated cervical cerclage insertion in a low-resource setting

Abstract: The limitations of the study notwithstanding, use of history-indicated cervical cerclage in pregnancy resulted in better fetal salvage rate and reduced recurrence of spontaneous miscarriage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…29 Previable and preterm delivery rates in this study were 7.5% and 17.5% respectively, However, an earlier study in Lagos southwest Nigeria found a lower pre-viable delivery rate of 5.6% but a higher preterm birth rate of 30%. 31 In our study, 75% of our clients sustained their pregnancies till term hence the increased incidence of spontaneous vaginal delivery in 62.5% of our clients on cervical cerclage while only 30% had either elective or emergency cesarean delivery. Cervical cerclage placement was successful in 75% of our clients while in 25% we had failed cerclage.…”
Section: Discussionmentioning
confidence: 52%
“…29 Previable and preterm delivery rates in this study were 7.5% and 17.5% respectively, However, an earlier study in Lagos southwest Nigeria found a lower pre-viable delivery rate of 5.6% but a higher preterm birth rate of 30%. 31 In our study, 75% of our clients sustained their pregnancies till term hence the increased incidence of spontaneous vaginal delivery in 62.5% of our clients on cervical cerclage while only 30% had either elective or emergency cesarean delivery. Cervical cerclage placement was successful in 75% of our clients while in 25% we had failed cerclage.…”
Section: Discussionmentioning
confidence: 52%
“…In a similar study in Abuja North Central Nigeria, (75) 78.1% of the women had history indicated cerclage, (21) 21.9% had rescue cerclage, while none had ultrasound indicated cerclage (Adewole et al, 2018). In other studies in Irua, Edo State South-South Nigeria and Nairobi Kenya, most of the patients had history indicated cerclage (Okusanya & Isabu, 2015;Kaura et al, 2013). The high number of patients that had history indicated cerclage in these studies may be due to the fact that ultrasound scan was used for few patients in the studies.…”
Section: Discussionmentioning
confidence: 88%
“…The major finding in our study was the success rate of 79.3% following cervical cerclage. Most studies have similar success rate (Ikimalo et al, 2012;Adewole et al, 2018;Okusanya & Isabu, 2015). This is a major pointer to the effectiveness of cervical cerclage in preventing midtrimester pregnancy loss and preterm labour.…”
Section: Discussionmentioning
confidence: 96%
“…Similar results were found in the literature regarding history-indicated elective cerclage, achieving prevention of second trimester loss (STL) or preterm birth (PTB) in two thirds of low-risk groups (defined by one or two prior STL or PTB or by one previous successful cerclage). [6][7][8] In this study one limitation may result from indication criteria. The indication for cerclage was at least one previous second trimester spontaneous pregnancy loss where no other cause was identified, conflicting with some recommendations were history of more pregnancy losses is required, hampering comparison.…”
Section: Discussionmentioning
confidence: 99%